Pemberdayaan Masyarakat Miskin: Pendekatan Modal Manusia (Studi Layanan Publik tentang Pemberdayaan Masyarakat Miskin yang Diselenggarakan oleh BPM-KB dan Posko 100 di Kota Surabaya) - Rulam Ahmadi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2012)
Poverty is one of development problems in developed and developing country like Indonesia. Poverty is complex problem that impacts negatively toward many aspects of people themselves, society and nation. Therefore, government has main duty to solve poverty problem comprehensively and holistically. Poverty occurs in Indonesia both in urban and rural area especially in Surabaya. There are many program of poverty alleviation that have been implemented or being implemented by government and community. One of poverty alleviation programs in Surabaya is poor people empowerment which it has been implemented by Community Empowerment Board-Family Planning and Posko 100. Those programs emphasize on firstly human capital development which is harmonized with other empowerments and participatory development (partnership). Poor people empowerment in Surabaya that has been implemented by Community Empowerment Board-Family Planning and Posko 100 is one way of public service namely providing training service, providing facilities, and developing partnership. Theoretically, public service relates to main ideas of Denhardt and Denhardt (2000) about new public service, human capital approach relates to concept of Theodore W. Schultz (Fagerlind and Saha, 1983) and Gary S. Becker (Seo, 2005; Lauri, 2004), and non-formal training relates to Philip H. Combs and Manzoor Ahmed (1973). Empowerment dimensions relate to concepts of Rappaport (Suharto, 2007:59; Nawawi, 2007:176), and concept of the World Bank (Narayan, 2002). The purposes of the study are to identify (1) the process of poor people empowerment, (2) participation of private sector, society, and trainee in poor people empowerment program, (3) the roles of government in empowering poor people, (4) the result of poor people empowerment, and (5) models of poor people empowerment that have been implemented by Community Empowerment Board-Family Planning and Posko 100 in Surabaya. Keywords: Public Service, Poverty, Empowerment, Human Capital, Participation, Community Empowerment Board-Family Planning (BPM-KB) and Posko 100